Vehicle ride comfort analysis on sea-crossing bridges under drift ice load. (January 2023) - Wu, Tianyu; Qiu, Wenliang; Yao, Guowen; Guo, Zengwei
Abstract: To investigate the ride comfort when vehicles travelling over sea-crossing bridges subjected to ice load in cold sea regions, this study presented a dynamic analysis framework for a vehicle–bridge interaction system under ice-induced vibration. Based on the a real ice load spectrum in Bohai Sea, the ice force process during the interaction between ice and bridge is obtained, and is input into the vehicle-bridge coupling system as an external excitation. This framework was assessed with an interactive system consisting of 6 12-DOF trucks travelling over the pile-supported sea-crossing bridges. Ride comfort of vehicles is investigated under different conditions of vehicle velocity and ice strength and it is evaluated by utilizing newly recommended in the ISO 2631-1(1997). The results show that the vibration of the vehicle will not influence driving comfort of the driver when vehicles traveled over bridges without considering the actions of ice load. However, the evaluation indicator of driving comfort reached a little uncomfortable when vehicles traveled over bridges under ice strength exceeds 1.5 MPa. In addition, the ride comfort analysis based on ISO 2631/1(1985) was also investigated. But the criterion only evaluates the comfort in one direction, and it is disadvantageous for the quantitative evaluation of driving comfort and it may underestimate the overall vibration of vehicles and total evaluation results of vehicle ride comfort.